Pengaruh Kepemimpinan Guru Terhadap Sikap Hormat Siswa Kepada Guru Di Smp Lokon St. Nikolaus Tomohon - Labuan, Bernadina Waha; Turang, Kevin Giovani (Syntax Corporation, 2025)
This study examines the influence of teacher leadership on students' respect attitudes at SMP Lokon St. Nikolaus Tomohon. Students' respect attitudes are influenced by good teacher leadership styles. This research uses a quantitative approach with a sample of 150 students and is analyzed using simple linear regression through IBM SPSS 25 software. The results show that teacher leadership has a positive and significant effect on students' respect attitudes. Good leadership styles, such as setting an example and showing concern, enhance students' respect, while authoritarian or indifferent styles can decrease respect. These findings emphasize the crucial role of teacher leadership in creating a learning environment filled with appreciation and mutual respect.